Assessment to Measure Problem Solving Ability in the Lesson of the Interaction of Living Things with the Environment - Raden Gamal Tamrin Kusumah; Rambat Nur Sasongko; Muhammad Kristiawan; Ahmad Walid; Meri Andaria (Jurnal Studi Guru dan Pembelajaran, 2021)
This study aims to determine the form of assessment development to measure students' problem solving abilities. This research uses a type of Research and Development (R & D) with a quantitative approach. The research procedure refers to the Borg & Gall development model, which includes 8 steps, namely potential problems, information gathering, product development, expert validation, expert revision, small group trials, product revision, final product. The research instruments used were questionnaires, interviews, and documentation. The research was conducted in 3 schools in Bengkulu City. The resulting assessment has categories, namely defining problems, examining problems, planning solutions, implementing plans that have been made, evaluating. After carrying out various kinds of expert tests, this question instrument has been valid and reliable, so it is appropriate to be disseminated to the school community